Credit Risk Spillovers Among Financial Institutions Around the Global Credit Crisis: Firm-Level Evidence - Yang, Jian; Zhou, Yinggang (Management Science, 2013)
Using credit default swap data, we propose a novel empirical framework to identify the structure of credit risk networks across international major financial institutions around the recent global credit crisis. Specifically, we identify three groups of players, including prime senders, exchange centers, and prime receivers of credit risk information. Leverage ratios and, particularly, the short-term debt ratio appear to be significant determinants of the roles of financial institutions in credit risk transfer, while corporate governance indexes, size, liquidity, and asset write-downs are not significant. Our findings carry important implications for a new regulatory standard on capital subcharge and liquidity coverage ratio. This paper was accepted by Wei Jiang, finance.